Morphological Response in Cancer Spheroids for Screening Photodynamic Therapy Parameters - Aguilar Cosme, Jose R.; Gagui, Dan C.; Bryant, Helen E.; Claeyssens, Frederik (Frontiers in Molecular Biosciences, 2021)
Photodynamic therapy (PDT) is a treatment which uses light-activated compounds to produce reactive oxygen species, leading to membrane damage and cell death. Multicellular cancer spheroids are a preferable alternative for PDT evaluation in comparison to monolayer cell cultures due to their ability to better mimic in vivo avascular tumour characteristics such as hypoxia and cell-cell interactions, low cost, and ease of production. However, inconsistent growth kinetics and drug responsiveness causes poor experimental reproducibility and limits their usefulness. Herein, we used image analysis to establish a link between human melanoma C8161 spheroid morphology and drug responsiveness. Spheroids were pre-selected based on sphericity, area, and diameter, reducing variation in experimental groups before treatment. Spheroid morphology after PDT was analyzed using AnaSP and ReViSP, MATLAB-based open-source software, obtaining nine different parameters. Spheroids displayed a linear response between biological assays and morphology, with area (R2 = 0.7219) and volume (R2 = 0.6138) showing the best fit. Sphericity, convexity, and solidity were confirmed as poor standalone indicators of spheroid viability. Our results indicate spheroid morphometric parameters can be used to accurately screen inefficient treatment combinations of novel compounds.